Chemical Design of Carbon-Coated Al2O3 Nanoparticles - L. F. Sharanda; I. V. Babich; Yu. V. Plyuto (Хімія, фізика та технологія поверхні, 2010)
The novel approach to chemical design of carbon-coated Al2O3 nanoparticles with an average particle size of 8-10 nm was developed. Carbon coating was synthesised by modification of fumed alumina support with 4,4’-methylenebis-(phenylisocyanate) and its subsequent pyrolysis at 700oC. In order to synthesise the samples with increased carbon content, the grafting-pyrolysis cycle was repeated. The above mentioned synthetic route resulted in the samples with carbon loading of 7.6 and 14.5 wt.%. Characterisation of the synthesised samples with Raman, FTIR, TG/DTG-DTA, N2 adsorption and SEM techniques revealed the formation of continuous carbon coating on the surface of Al2O3 nanoparticles after the first grafting-pyrolysis cycle. The increase of the carbon loading on the alumina surface to 14.5 wt.% (two grafting-pyrolysis cycles) resulted in the formation of the carbon coating with more regular graphitic structure.